ENVIRONMENTAL GEO-INFORMATIONAL MONITORING SYSTEM FOR THE CIVIL AND FIRE SAFETY SERVICES OF UKRAINE - STARODUB, Yuriy; MYKHALICHKO, Borys; LAVRENYUK, Helen; KOZIONOVA, Olesia; POŁCIK, Henryk; KUPLOVSKYI, Bohdan (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background.The purpose of the work is the development of a new ecological and geo-informational system for monitoring emergency situations, which allows quick predicting the consequences of various natural and man-made hazards at the stage of preventing their occurrence. This applies to possible cases of destruction on territories where there is a threat of flooding and, accordingly, the protection of coasts, structures, roads on mountain slopes, bridges, tunnels and dams built on soils with certain geological and geophysical characteristics, as well as the occurrence and spread of fires and pollution of air, water and soil with harmful substances associated with them. Methods. To implement the methods, available and purchased licensed software is used, creating convenient algorithms for solving practical tasks of civil protection. Information processing based on the used software packages that allow quickly processing large amounts of information, reducing the level of poor processing and data distortion. Results. An ecological and geo-informational monitoring system has been developed, designed to ensure the coordination of actions of civil and fire protection services in order to increase the efficiency of responding to emergency situations of natural and manmade origin. By conducting experiments, model results were obtained, which make possible to theoretically calculate and determine the critical permissible stress-deformed states of the soil massif in the area of engineering structures, bridge structures, to warn about the possible destruction of the massif due to excess stress and deformation under the action of loads. Proposed localization of fire-hazardous zones based on satellite data. As part of the developed system for space monitoring of forest fires, satellite information is used, in particular, the AVHRR radiometer of the Terra satellite. On its basis, a temperature map of the regions of Ukraine was formed. Conclusions. The geo-informational monitoring system was created to prevent the risks of emergency situations (including the destruction of slopes, fires, etc.) using software products, creating databases for mapping potentially dangerous objects. Its application will make it possible to assess the consequences of possible emergency situations of a natural and man-made nature and minimize their negative impact on the environment. The developed geo-information system can be used to coordinate the actions of civil and fire protection services, as well as increase the efficiency of emergency and rescue measures.